REMODELING UTERINE SCAR AFTER MIOMECTOMY AND THE ROLE OF DOPPLEROMETRY IN ITS EVALUATION - E. V. Bashirov; I. I. Kutcenko; V. A. Krutova; A. V. Babkina (Кубанский научный медицинский вестник, 2017)
Aim. The aim of the study: to compare the effectiveness of traditional laparoscopic myomectomy to the one with an additional stage based on the analysis of echographic scar monitoring among fertile-interested patients.Materials and methods. A prospective analysis of 96 surgical interventions was performed (laparoscopic myomectomy among reproductive-aged patients with uterine fibroids (UF).Results. Echographic scar monitoring showed a lower incidence of adverse sonographic stigma after laparoscopic occlusion of the ascending branches of the uterine artery (UA AB LSO) during three months’ time observation and a leveling of differences – during half a year.Conclusions. UA AB LSO improves the quality of myomectomy and the probability of morphologically substantiated scar formation on the uterus.